2019
DOI: 10.1177/1745499919829217
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive assessment tool designed for data collection in the field in low- and middle-income countries

Abstract: The Rapid Assessment of Cognitive and Emotional Regulation (RACER) is a tablet-based assessment tool for children that measures executive function (EF) skills. Instructions that are brief and visually presented; gamelike tasks are designed to easily engage children regardless of literacy level and variable test administration settings. RACER measures inhibitory control and working memory. This study presents the theoretical rationale and empirical evidence for tablet-based assessments of EF, the process of adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 85 publications
1
31
0
Order By: Relevance
“…By contrast, Jordanian peers experienced less exposure to both poverty and the violence of war. We measured EF using computerized assessments (RACER tasks), observing task manipulation effects similar to those observed in Lebanon (Ford et al, 2019), Niger (Ford et al, 2019), and the United States (Sheridan, Kharitonova, Martin, Chatterjee & Gabrieli, 2014). Recent work based on the United States has demonstrated a disassociation between trauma and poverty in predicting EF, whereby exposure to poverty but not traumatic violence predicts EF task performance (Lambert et al, 2016;Sheridan et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…By contrast, Jordanian peers experienced less exposure to both poverty and the violence of war. We measured EF using computerized assessments (RACER tasks), observing task manipulation effects similar to those observed in Lebanon (Ford et al, 2019), Niger (Ford et al, 2019), and the United States (Sheridan, Kharitonova, Martin, Chatterjee & Gabrieli, 2014). Recent work based on the United States has demonstrated a disassociation between trauma and poverty in predicting EF, whereby exposure to poverty but not traumatic violence predicts EF task performance (Lambert et al, 2016;Sheridan et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, Jordanian peers experienced less exposure to both poverty and the violence of war. We measured EF using computerized assessments (RACER tasks), observing task manipulation effects similar to those observed in Lebanon (Ford et al, ), Niger (Ford et al, ), and the United States (Sheridan, Kharitonova, Martin, Chatterjee & Gabrieli, ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We found that average cortisol levels dropped by a third (38%) in response to the program; stress was down-regulated in youth with high cortisol levels and up-regulated in youth with blunted cortisol profiles, showing beneficial regularization over time [13,14]. [15] to measure working memory and inhibitory control, both important for learning abilities. We found no program impacts on these executive function skills, but showed that deficits in working memory were associated with pervasive poverty, rather than trauma exposure [16].…”
Section: Scientific Importancementioning
confidence: 88%